Dysferlin deficiency confers increased susceptibility to coxsackievirus‐induced cardiomyopathy. (16th July 2015) - Wang, Chen; Wong, Jerry; Fung, Gabriel; Shi, Junyan; Deng, Haoyu; Zhang, Jingchun; Bernatchez, Pascal; Luo, Honglin
Summary Coxsackievirus infection can lead to viral myocarditis and its sequela, dilated cardiomyopathy, which represent major causes of cardiovascular mortality worldwide in children. Yet, the host genetic susceptible factors and the underlying mechanisms by which viral infection damages cardiac function remain to be fully resolved. Dysferlin is a transmembrane protein highly expressed in skeletal and cardiac muscles. In humans, mutations in the dysferlin gene can cause limb‐girdle muscular dystrophy type 2B and Miyoshi myopathy. Dysferlin deficiency has also been linked to cardiomyopathy. Defective muscle membrane repair has been suggested to be an important mechanism responsible for muscle degeneration in dysferlin‐deficient patients and animals. Using both naturally occurring and genetically engineered dysferlin‐deficient mice, we demonstrated that loss of dysferlin confers increased susceptibility to coxsackievirus infection and myocardial damage. More interestingly, we found that dysferlin is cleaved following coxsackieviral infection through the proteolytic activity of virally encoded proteinases, suggesting an important mechanism underlying virus‐induced cardiac dysfunction. Our results in this study not only identify dysferlin deficiency as a novel host risk factor for viral myocarditis but also reveal a key mechanism by which coxsackievirus infection impairs cardiac function, leading to the development of dilated cardiomyopathy.